(3eLehYI GdChdjGA (B_ (3efXheIs - (3GdTjN haG GdQaGYj , eMeO Hf eMeO Hf YeQ Hf TGgjf GdQaGYj GdMdHj, CHh GdhaGA,J (B1264 (3g` s ((3Ydi ceGd GdeOQSi s)
(3ChdgG (B:s
(3HOFi HHSe Gddg ajg GdHQcI hMeOg jef dcd MQcg aEdjg HGdPcQ YXje GdejefI hef OhGYi GdbWY agh s
(3BNQgG (B:s
(3fSFdI HhLgg GdcQje QDjJg ai LfI GdfYje s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B73 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B254s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs